Bronchoalveolar Lavage Fluid Cytology in Healthy Cynomolgus Macaques - Pavot, Vincent; Prost, Christine; Dubost-Martin, Guillaume; Thibault-Duprey, Kevin; Ramery, Eve (Frontiers in Veterinary Science, 2021)
Bronchoalveolar lavage, or BAL, is a minimally invasive procedure frequently used for clinical and non-clinical research, allowing studies of the respiratory system. Macaques are the most widely used non-human primate models in biomedical research. However, very little information is available in the literature concerning BAL cytology in macaques. The purpose of this study was to establish BAL reference values and document an atlas of BAL cytology from healthy cynomolgus macaques. BALs were obtained from 30 macaques and BAL fluid differential cell counts based on 400 nucleated cells/BAL sample were performed by a board-certified clinical pathologist. Results were analyzed using Reference Value Advisor macroinstructions and the effect of blood and oropharyngeal contaminations was investigated. Overall, nucleated cells interval percentages in BAL fluids were 55.8 to 93.7 for macrophages, 1.8 to 37.1 for lymphocytes, 0.4 to 8.7 for neutrophils, and 0.4 to 9.8 for eosinophils. Mild oropharyngeal contamination did not affect BAL differential cell counts, whilst a slight but significant increase of the percentage of lymphocytes was observed in samples with mild blood contamination. Mucus and variable numbers of ciliated epithelial cells were commonly present. Rarely, multinucleated macrophages and mastocytes were also observed. The reference intervals established in this study provide a useful baseline for the assessment of BAL cytological data in cynomolgus macaques.